FIGUR DAHLAN ISKAN DALAM KOLOM MANUFACTURING HOPE SUMUT POS KAJIAN: TEKNIK PENGEMBANGAN DAN NADA TULISAN - Endang Wahyuningsi (JURNAL PENDIDIKAN ROKANIA, 2017)
The purpose of this researched was to figure Dahlan Iskan through engineering development and writing tone in column “Manufacturing Hope Sumut Pos”. This research is qualitative research that had description method. The object in the reseacrh is column “Manufacturing Hope Sumut Pos at 6, 13, and 20 Mei 2013. This data collecting technical is documentation. The results of this research showed two things. First, by engineering development can know that Dahlan Iskan Figure is someone that as at is, to be responsible, and appreciate a person or the opinions of others, and someone a have dreams or hope so tha bettert Indonesia BUMN. Second, by writing tone Dahlan Iskan Figure is wise, optimistic, and have a good thought about the future Indonesia BUMN, however, Dahlan Iskan have defestism, worried, and agitated, next, by the attitutde of the author to reader, then Dhalan Iskan is the all knowing compared with reader